Influence of mixed boundary conditions and heterogeneity on the vibration behavior of orthotropic truncated conical shells - Sofiyev, A.H.; Huseynov, S.E.; Kuruoglu, N. (Archives of Mechanics, 2015)
This paper presents the vibration behavior analysis of heterogeneous orthotropic conical shells with mixed boundary conditions. Basic equations of heterogeneous orthotropic truncated conical shells are derived using Donnell–Mushtari shell theory. Employing the separation of variables and Galerkin's method, the expressions for frequency of heterogeneous orthotropic conical shells with two mixed boundary conditions are obtained. The results are validated through numerical comparisons with available results in the literature. The influences of truncated shell characteristics, heterogeneity, material orthotropy and mixed boundary conditions on dimensionless frequency parameters are investigated.